THE INFLUENCE OF GLOBALIZATION ON THE SPREAD OF ENGLISH AS A LINGUA FRANCA - Muborova Zarina The student of Chirchik State Pedagogical University muborovazarina@gmail.com, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
The rise of globalization has significantly influenced the dominance of English as a global Lingua Franca. This article examines the interplay between globalization and the expansion of English, exploring its adoption across various sectors such as business, education, technology, and diplomacy. By analyzing sociolinguistic and economic factors, the study highlights how globalization has catalyzed the spread of English while considering the cultural and linguistic consequences. Furthermore, the article discusses the implications of English’s dominance for multilingualism and cultural identity. Through a critical side, the article also reflects on the challenges and opportunities associated with the global status of English.